2004
DOI: 10.1038/sj.npp.1300506
|View full text |Cite
|
Sign up to set email alerts
|

Discovering Endophenotypes for Major Depression

Abstract: The limited success of genetic studies of major depression has raised questions concerning the definition of genetically relevant phenotypes. This paper presents strategies to improve the phenotypic definition of major depression by proposing endophenotypes at two levels: First, dissecting the depressive phenotype into key components results in narrow definitions of putative psychopathological endophenotypes: mood bias toward negative emotions, impaired reward function, impaired learning and memory, neuroveget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
746
3
15

Year Published

2005
2005
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 1,026 publications
(783 citation statements)
references
References 183 publications
(173 reference statements)
19
746
3
15
Order By: Relevance
“…Moreover, reward dependence, a putatively heritable trait associated with maintenance of behavior in response to reward cues, shows trait-like features associated with familiality of depression (Farmer et al, 2003). Collectively, these findings suggest that anhedonia is among the most promising endophenotypes of depression (Hasler et al, 2004). Still, little is know about which aspects of hedonic processing might be dysfunctional in depression.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, reward dependence, a putatively heritable trait associated with maintenance of behavior in response to reward cues, shows trait-like features associated with familiality of depression (Farmer et al, 2003). Collectively, these findings suggest that anhedonia is among the most promising endophenotypes of depression (Hasler et al, 2004). Still, little is know about which aspects of hedonic processing might be dysfunctional in depression.…”
Section: Discussionmentioning
confidence: 99%
“…Anhedonia, the decreased response to pleasurable stimuli, is a defining symptom of the disorder to the extent that MDD may be diagnosed even in the absence of depressed mood if anhedonia and other secondary symptoms are present [1]. Anhedonia is also a central feature of a number of neurobiological theories of depression that posit that deficits in emotional and motivational responses to appetitive stimuli are core features of the disorder [188], and the anhedonic endophenotype of MDD is perhaps the most well supported [10]. …”
Section: Reviewmentioning
confidence: 99%
“…The importance of anhedonia in psychopathology has recently been stressed by researchers who demonstrated that this symptom, together with increased stress reactivity, is an important candidate for psychopathological endophenotype of MDD. 9,10 Endophenotypes are subclinical traits that are associated with the expression of an illness and represent the genetic liability of the disorder in non-affected individuals. 1 The neural system underlying reward and pleasure is well defined in humans.…”
Section: Introductionmentioning
confidence: 99%